2006
DOI: 10.1021/jp055608e
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Isomerization Kinetics of Diiodomethane in Supercritical Fluid Solution:  Local Density Effects

Abstract: The density dependence of diiodomethane photoinduced isomerization in supercritical (sc) CO2, CHF3, and C2H6 was investigated by transient absorption spectroscopy, covering a fluid density range from 0.7 to 2.5 (in reduced units). The solvent-caged photoproduct iso-diiodomethane is formed even at the lowest density, and its yield increases about 4-fold over the whole range. At the same time, isomer formation rate constants increase by roughly an order of magnitude and show little variation between CO2, C2H6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…It was previously demonstrated that condensed phase environments promote a new photochemical path leading to the formation of metastable iso-polyhalomethane species. [2][3][4][5][6][7][8][9][10][11][12][13][14] The known functions of these reaction intermediates include the production of ions in the ocean 15 and photocyclopropanation reactions of olefins in solution. [16][17][18] In this regard, one of the most extensively investigated compounds is diiodomethane ͑CH 2 I 2 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that condensed phase environments promote a new photochemical path leading to the formation of metastable iso-polyhalomethane species. [2][3][4][5][6][7][8][9][10][11][12][13][14] The known functions of these reaction intermediates include the production of ions in the ocean 15 and photocyclopropanation reactions of olefins in solution. [16][17][18] In this regard, one of the most extensively investigated compounds is diiodomethane ͑CH 2 I 2 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors used them as solute models for predictions of the Henry's law constant: Boutard et al [15] for O 2 in ethanol, Krishnamurthy et al [16] for N 2 and O 2 in ethylene oxide and Shah and Maginn [17] for C 2 H 6 and C 2 H 4 in an ionic liquid. Grimm et al [18] used the CH 2 I 2 model to investigate local density effects on photoinduced isomerization kinetics of this substance in supercritical CO 2 . Müller et al [19,20] used several models (C 2 H 6 , C 2 H 4 , N 2 and C 2 F 6 ) for simulations on adsorption regarding micro-porous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…[71] As equential molecular dynamics (MD) andq uantum mechanics approach was used by Millot et al to compute the UV/Vis spectrum of organic dyes, [72] and more recently Born-Oppenheimer MD simulations were performed by Canuto's group to study the electronic spectrum of para-nitroaniline. [73,74] The organization of the solvent around the solute and its influence on the solution structural and dynamic properties were investigated by means of MD for small solutes, [75][76][77][78][79][80][81][82][83][84] polymers [85,86] and proteins, [87] and passivated gold nanoparticles. [88] Some work based on Car-Parrinello MD was also performed.…”
Section: Computational Studies Of Solvation In Pure Sccomentioning
confidence: 99%